Instagram Through Her Eyes: Exploring Female Instagram Content Creators’ Motivations for Content Creation - Mlangeni, Senamile; Nyawo, Thulebona; Nyathi, Mpumelelo; Mhlongo, Xolani Vincent; Mutanga, Murimo Bethel (Indonesian Journal of Information Systems, 2025)
Instagram has emerged as a dominant social media platform globally, particularly among young female users who engage actively with visual content and digital narratives. While existing studies have explored the psychological implications of social media usage, few have specifically focused on the motivations behind content creation and the nature of posts, especially within the context of South African universities. This study investigates these motivations among female students aged 18–35 at a University of Technology. A mixed-methods approach was employed, incorporating structured surveys, semi-structured interviews, and content analysis of Instagram posts over a three-month period. The findings indicate that motivations such as self-expression and validation underpin much of the content shared. The study contributes to the understanding of online identity construction and emotional regulation in digital spaces, offering insights into mental health awareness, digital literacy education, and inclusive platform design. By examining female students' Instagram engagement in the Global South, this research fills a contextual and theoretical gap, shedding light on the intersection of social media with unique cultural, academic, and technological dynamics.